Interventions to improve Quality of Sleep among patient Post Coronary Artery Bypass Graft (CABG) in ICU: a Scoping review - Nugraha, Bambang Aditya; Pebrianti, Sandra; Pratiwi, Sri Hartati; Nursalma, Aisyah; Amalia, Fany; Karina, Grashiva; Wahyuni, Indah; Nurjanah, Ismirani; Azizah, Levina; Ramdhani, Muhammad; Khairunnisa, Nisrina; Wati, Putri; Herman, Regina; Tanjung, Rifani; Salwa, Sayyidah (Universitas Padjadjaran, 2024)
Coronary Heart Disease (CHD) was the number two cause of death; one of the treatments for CHD was Coronary Artery Bypass Graft (CABG). Patients after undergoing CABG will undergo treatment in the Intensive Care Unit (ICU). In patients who experience treatment in the ICU, many patients experience sleep disturbances related to therapy regime rhythm in the ICU. This literature review aims to identify the intervention for managing sleep quality in post-CABG patients undergoing treatment in the ICU. The method use was a narrative review study, The review was conducted two databases, PubMed and ScienceDirect, to search data from 2012 to 2022. The keywords used were Coronary Artery Bypass Graft, Intensive care unit, and Sleep Quality. The results of this study included nine articles reviewed, which were entirely randomized control trials and randomized clinical trials. The review found that the interventions to manage sleep quality are deep breathing therapy, aromatherapy with roses, acupressure, self-care, and drug administration. From the results of the review, it was found that all articles reported using several specific interventions in the intervention group that were proven to improve sleep quality in post-CABG patients. The study results provide information for nurses regarding sleep quality in post-CABG patients.